The Agreeableness Type of Personality and the Basic Personal Values - Abdi, Fitore Bajrami (European Journal of Multidisciplinary Studies, 2017)
The goal of this study is to discover the relationship between the agreeableness type of personality and the basic personal values, analyzed through non-experimental methodology and quantitative approach. The sample of this study is the Albanian high school seniors in Skopje, Republic of Macedonia which consists of 479 subjects, randomly selected from the total sample specified. The subjects’ willingness to participate in the survey and their anonymity was respected by following all ethical norms. The results of correlative statistics show that there is association between the agreeableness type and all basic personal values, while the comparative statistics indicate statistically significant differences between the basic personal values related to the agreeableness type of personality and the highest mean score was reached by the value universalism. The Eta square agreeableness type of personality results showed a relatively low effect on the values stimulation as well as hedonism.
Keywords: personality, agreeableness type, basic personal values.